Effect of Swine Bone Powder for Reduce Cadmium Uptake by Rice - PECHRSAN, Sasithorn; SRISATIT, Thares (Journal of Environmental Management and Tourism, 2020)
The effect of swine bone powder application on bioavailability of Cd in contaminated soil from Tak Province, Thailand were conducted. The bioavailability of Cd was investigated in term of the uptake by rice plant (Oryza sativa L.) in green house at three different application rates of swine bone powder amended soil, including 5, 10 and 15%, respectively. The result demonstrated that the efficiency of cadmium uptake in Khao Dawk Mali 105 rice were in range 0.18-0.20 % and the 5% swine bone amended soil had a positive effect on promoting plant growth and seed yield. Cd concentration in both of shoot and roots decreased with increasing the swine bone application rates. Cadmium bioaccumulation in plant root to soil and translocation factor from root to shoot was less than one. The results indicated that swine bone powder-amended soil could be an alternative and cost-effective method to support plant growth and decrease Cd mobility in soil.